Analysis of Excavator Work Efficiency by Appyling Chronometry Method (Proceedings of Faculty of Civil Engineering, 2019)
Problems within the area of production organization, which are solved by scientific discipline of the work-study, have begun to be systematically dealt with in our region during 1960s, and method development (such as chronometry) persists today. The significance of the work-study is the attempt to rationalize the work organization through the definition and monitoring of the constituent elements of working time with the aim of establishing the norms that will be valid for the work operation as a whole. The calculation of construction machinery practical effect is of great importance for determining the more realistic duration of machine work on construction site, and thus the more accurate prediction of the whole construction project duration. The main topic of this paper is the time study analysis of a standard cyclic construction machine in its one technological process. At the same time, the work operation of the excavator loading into transportation vehicle has been observed and analyzed. Data were obtained by snapback chronometry method with the purpose of determining work efficiency i.e. defining the actual excavator work efficiency during the operation of loading. The data obtained by measurement were analyzed and the actual time of defined technological process was calculated as well as a corresponding normative. Moreover, a comparison was made with the calculation of excavator practical effect, which was calculated using the standardized tables for the calculation of standard cyclic construction machine. The comparison resulted in differences between these two approaches. The identified deviations were analyzed as well as the reasons for their occurrence and conclusions were drawn resulting in recommendations for updating the existing standardized tables for the calculation.
Keywords: excavator; chronometry method; measurement; work-study; efficiency